2008
DOI: 10.1016/j.surg.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

A novel method of 2-channel dual-pulse gastric electrical stimulation improves solid gastric emptying in dogs

Abstract: Background-Gastric electrical stimulation (GES) is known to improve vomiting with short pulses, normalize dysrhythmia with long pulses, and accelerate gastric emptying with two-channels. The aim of this study was to assess the effects of a new method GES -two-channel GES with dual pulses on gastric emptying of solids as well as gastric dysrhythmia and emetic responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…172 Another direction of research involves dual pulse stimuli with alternating delivery of short neuro stimulation and long pacing pulses to elicit antiemetic and motor stimulatory effects with a single device. 173 Percutaneous and endoscopic systems to implant elec trodes in the gastric wall without surgery may broaden the applicability of electrical pacing technologies. 174 Other surgical treatment Other surgeries are rarely performed in patients with refractory gastroparesis.…”
Section: Gastric Electrical Stimulationmentioning
confidence: 99%
“…172 Another direction of research involves dual pulse stimuli with alternating delivery of short neuro stimulation and long pacing pulses to elicit antiemetic and motor stimulatory effects with a single device. 173 Percutaneous and endoscopic systems to implant elec trodes in the gastric wall without surgery may broaden the applicability of electrical pacing technologies. 174 Other surgical treatment Other surgeries are rarely performed in patients with refractory gastroparesis.…”
Section: Gastric Electrical Stimulationmentioning
confidence: 99%
“…Short-pulse GES has been reported to improve nausea and vomiting in gastroparetic patients with limited or no effects on gastric motility or slow-wave stabilization (1,3,31). Dual-pulse GES, combined with both short pulses and long pulses, has advantages of both long-pulse GES and short-pulse GES and is capable of improving dysrhythmia and nausea and vomiting (48). Recently, a number of studies have shown that synchronized GES (or SGES, electrical stimuli are delivered at the occurrence of intrinsic slow waves) has a prokinetic effect: increasing antral contractions and accelerating gastric empty (47,57,59).…”
mentioning
confidence: 99%
“…This observation was also in agreement with the results on multichannel gastric pacing previously published in both healthy and diseased canine models. [18][19][20] One of the major drawbacks for single-channel gastric pacing with long pulses is that it needs high stimulation energy to entrain gastric slow waves and normalize dysrhythmias. This is explained by the fact that the stimulating electrode has to be placed in the proximal stomach to avoid reverse pacing.…”
Section: Gastric Pacingmentioning
confidence: 99%
“…This is explained by the fact that the stimulating electrode has to be placed in the proximal stomach to avoid reverse pacing. 20 To entrain gastric slow waves, the stimulation energy for the single-channel gastric pacing has to be high enough to ensure the stimulation pulses are propagated a distance of 20 cm or greater from the proximal stomach to the distal antrum. Therefore, multichannel GES was designed to mimic the natural propagation and characteristics of the gastric slow waves.…”
Section: Gastric Pacingmentioning
confidence: 99%